2012
DOI: 10.1089/jmf.2012.2231
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Isolated from Angelica sinensis Inhibits Hepcidin Expression in Rats with Iron Deficiency Anemia

Abstract: A novel polysaccharide named Angelica sinensis polysaccharide (ASP) was obtained from the powdered and defatted roots of A. sinensis (Oliv.) Diels. The molecular weight of ASP was determined to be 78 kDa and was 95.0% sugars consisting of mostly arabinose, glucose, and galactose with a molar ratio of 1:5.68:3.91. A previous study indicated that ASP may increase plasma iron levels by suppressing the expression of hepcidin, a negative regulator of body iron metabolism, in the liver. The present study aims to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…Asinensis sinensis was found to be effective for enhancing haematopoiesis by increasing the secretion of some haematopoietic growth factors (EPO) via stimulating haematopoietic cells and muscle tissues (Sarker & Nahar 2004). Roots of A. sinensis-containing ASP are reported to reduce anaemia (Liu et al 2012;Zahra et al 2016). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Asinensis sinensis was found to be effective for enhancing haematopoiesis by increasing the secretion of some haematopoietic growth factors (EPO) via stimulating haematopoietic cells and muscle tissues (Sarker & Nahar 2004). Roots of A. sinensis-containing ASP are reported to reduce anaemia (Liu et al 2012;Zahra et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…This effect on haematological parameters might be due to the depression of renin-angiotensin system by ACEIs, as this system is involved in the regulation of haematopoiesis (Cole et al 2000). This depression of renin-angiotensin system down regulates EPO which might affect the hepcidin expression and cause iron deficiency with anaemia (Handelman & Levin 2008;Liu et al 2012). In our study, the EPO-treated group showed improvement in the haematological parameters and anaemia induced by lisinopril (ACEI).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations